2012
DOI: 10.1172/jci38576
|View full text |Cite
|
Sign up to set email alerts
|

The ADP receptor P2RY12 regulates osteoclast function and pathologic bone remodeling

Abstract: The adenosine diphosphate (ADP) receptor P2RY12 (purinergic receptor P2Y, G protein coupled, 12) plays a critical role in platelet aggregation, and P2RY12 inhibitors are used clinically to prevent cardiac and cerebral thrombotic events. Extracellular ADP has also been shown to increase osteoclast (OC) activity, but the role of P2RY12 in OC biology is unknown. Here, we examined the role of mouse P2RY12 in OC function. Mice lacking P2ry12 had decreased OC activity and were partially protected from age-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
105
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 81 publications
5
105
1
3
Order By: Relevance
“…This decrease in bone mass was unexpected given the previously suggested role for the P2Y 1 receptor in osteoclast activity. However, a recent study found that ADP still stimulated osteoclast formation and resorption in cells derived from P2Y 1 receptor knockout mice [120], suggesting the involvement of another P2Y receptor. Based on pharmacology, the logical alternative candidate for mediating the effects of ADP on osteoclasts was the P2Y 12 receptor.…”
Section: Functional Effects Of P2 Receptor-mediated Signalling In Ostmentioning
confidence: 95%
See 4 more Smart Citations
“…This decrease in bone mass was unexpected given the previously suggested role for the P2Y 1 receptor in osteoclast activity. However, a recent study found that ADP still stimulated osteoclast formation and resorption in cells derived from P2Y 1 receptor knockout mice [120], suggesting the involvement of another P2Y receptor. Based on pharmacology, the logical alternative candidate for mediating the effects of ADP on osteoclasts was the P2Y 12 receptor.…”
Section: Functional Effects Of P2 Receptor-mediated Signalling In Ostmentioning
confidence: 95%
“…Analysis of P2Y 1 , P2Y 2 , P2Y 6 , P2Y 12 , P2Y 13 and P2X7 knockout mice has provided evidence for the important role of purinergic signalling in bone remodelling in vivo [115][116][117][118][119][120][121][122]. Previous reviews concerned with purinergic signalling on bone have focussed on different aspects, including bone marrow cells [123]; bisphosphonates [124][125][126] Widespread expression of P2X receptors on osteoblasts has also been reported.…”
Section: Bonementioning
confidence: 99%
See 3 more Smart Citations